The potential of green roofs in sustainable stormwater engineering in the eThekwini CBD - Sucheran, Arisha (My University, 2018)
Cities are facing serious problems relating to stormwater such as water scarcity, degraded waterways, increased flooding, and degradation of the quality of water. In response to these impacts, a number of sustainable urban drainage systems (SuDS) are being developed and implemented in many cities. In particular, green roofs boast an array of advantages, including their ability to delay and reduce stormwater runoff, and improve stormwater runoff quality. This study compares the water quality and quantity of green roofs with that of conventional roofs in the eThekwini region, and compiles a model using Personal Computer Storm Water Management Model (PCSWMM) to investigate the effect that incorporating the best performing green roof would have on stormwater flow rates and volumes for the region. In terms of water quality, the data analysis revealed significant variations in pollutant concentrations between the green roofs and the conventional roof. Metals such as arsenic, iron, and aluminium were found in high concentrations in green roof runoff. In terms of stormwater runoff quantity, the green roof systems proved to significantly reduce stormwater runoff flow rates and volumes. The highest retention rates were achieved for low intensity rainfall events, whilst the lowest was achieved for high intensity rainfall events. The implementation of green roofs within the eThekwini Central Business District (CBD) proved to be advantageous in reducing peak stormwater flow rates.
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering, Johannesburg 2018
Keywords: Stormwater infiltration; Storm sewers